The relationship between the most consumed digital media in Portugal and audience participation mechanisms - Sixto-García, José; Duarte-Melo, Ana; Andrade, José Gabriel (Frontiers in Communication, 2024)
Introduction Digital journalism is well established in Portugal. However, the Portuguese public tend to opt for traditional media websites over those of a digital native nature. This research will confirm whether the reason for the national success of the former type of media is that their websites offer more participation mechanisms for the publics. Methods Based on a qualitative methodology, an ad hoc methodological instrument was designed that allows for the evaluation of the ways in which audiences can interact with brands and content. Results and discussion The results are highly surprising, since it is not possible to verify any type of relationship between preferred media and the number of audience participation mechanisms. Experts on a Delphi panel attribute media selection to the audiences’ interest in the stories covered and to the trust placed in the media.